Empowerment Status of Sub-Marginal Women Farmers and Perceived Constraints in Livelihood Security (Indian Journal of Extension Education, 2016)
The study was taken up in Muzaffarpur district of Bihar with an objective to examine the empowerment status of sub marginal women farmer and their perceived constraints. The result revealed that majority of the respondents of experimental group had more power of decision making, positive thinking, and access of information with respect to control group. Water scarcity, timely unavailability of critical input in-time on reasonable price, appropriate infrastructure, and lack of technical expert are the key constraints and played a crucial role in their livelihood security. Meeting these constraints will certainly excel their agricultural productivity and bring improvement in their livelihood.